Assessment of Fungal and Contamination of Ochratoxin A and Patulin in Foods Susceptible to Contamination in the Yangzhou Market, China - Qinghua Gong; Zihan Zhang; Peiwen Huang; Bo Wang; Xiangfeng Zheng (Foods)
The conducive conditions of warm and humid climates can facilitate mold proliferation and subsequent mycotoxin production during food processing and distribution, thereby posing a potential risk to consumer health. However, there exists a significant lack of research regarding the diversity of molds and the presence of ochratoxin A (OTA) and patulin (PAT) in food products available in the Yangzhou market. This study was conducted to assess OTA contamination levels and fungal presence in 57 cereal-based food samples, as well as PAT contamination levels and fungal presence in 50 types of foods, including apples, hawthorn berries, pears, and their derivatives. Ochratoxin A (OTA) was detected in 17 out of 57 cereal-based food samples, with concentrations ranging from 0.93 to 32.69 μg/kg. The contamination rate was determined to be 31.48%, and no samples exceeded the established regulatory limits. Furthermore, seven apple products were identified as contaminated with patulin (PAT), exhibiting concentrations between 26.85 and 192.78 μg/kg. Additionally, three food samples derived from hawthorn showed PAT contamination levels ranging from 29.83 to 88.56 μg/kg. Through purification on potato dextrose agar (PDA) medium, observation of colony morphology, and analysis of internal transcribed spacer (ITS) sequences, a total of 35 fungal strains belonging to 13 genera were identified in cereal-based foods. The predominant genera in cereals included Talaromyces, Fusarium, Aspergillus, and Penicillium. Additionally, twelve fungal strains from five genera (Penicillium, Cladosporium, Aureobasidium, Curvularia, and Alternaria) were isolated and identified in fruits and their derivatives. The findings indicate that OTA and PAT toxins are one of the important risk factors that threaten consumer health. Furthermore, the contamination of some other toxigenic strains is also a matter of substantial concern, with potential implications for consumer health.